Between Hollywood glamour and bureaucratic grayness: film as a means of influencing the public opinion determinant of foreign policy - Stanković, Aleksandar (Napredak, 2025)
Film represents a powerful instrument capable of influencing public opinion. This paper therefore examines this medium and its impact on shaping foreign policy and determining the course a state pursues in international relations. Furthermore, it explores how different models of film vary in their influence on public opinion, as well as how they affect public attitudes toward specific issues. The theoretical foundations of foreign policy determinants, public opinion, and film are presented with the aim of identifying their common intersection—that is, the ways in which the cinematic medium can indirectly, through public opinion, influence foreign policy. The hypothesis positions film as one of the most significant factors in shaping the public-opinion determinant of foreign policy, while also partially addressing the effects it may have on the public.
Keywords: foreign policy analysis; determinants of foreign policy; public opinion; film; media